1998
DOI: 10.1007/s002689900379
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Gastric Cancer Patients after Total Gastrectomy

Abstract: A number of causes of malnutrition after total gastrectomy have been proposed. The purpose of this study was to assess nutritional status and to determine the cause of malnutrition after total gastrectomy. We studied 20 gastric cancer patients who had undergone total gastrectomy and immunochemotherapy and 6 normal controls. Nutritional status was assessed by dietary history, anthropometric methods, and serologic measurements. Malabsorption tests included the fecal fat excretion test, D-xylose absorption test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
97
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 33 publications
2
97
0
5
Order By: Relevance
“…Gastrectomy is the gold standard for curative treatment modality performed on gastric cancer patients (Brennan and Karpeh, 1996). Previous studies have shown that poor nutritional status was observed in patients who had undergone gastrectomy (Bae et al, 1998;Carey et al, 2011). After the operation, severe fat malnutrition and vitamin deficiency were found (Bae et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrectomy is the gold standard for curative treatment modality performed on gastric cancer patients (Brennan and Karpeh, 1996). Previous studies have shown that poor nutritional status was observed in patients who had undergone gastrectomy (Bae et al, 1998;Carey et al, 2011). After the operation, severe fat malnutrition and vitamin deficiency were found (Bae et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that poor nutritional status was observed in patients who had undergone gastrectomy (Bae et al, 1998;Carey et al, 2011). After the operation, severe fat malnutrition and vitamin deficiency were found (Bae et al, 1998). Major upper gastrointestinal surgery affects permanent alterations to the gastrointestinal tract, and therefore results in weight loss, body change, and malabsorption (Carey et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our study identifies some baseline HRQL items related to long-term greater BWL. Two studies have previously described 7-15% of BWL after gastric cancer resection (14,15). Another study has even identified cachexia in half of the patients (9).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that patients undergoing total gastrectomy will lose 7%-15% of their body weight, usually within the first year of surgery, and will not return to a preoperative weight (14)(15)(16). The reduction in calorie intake as well as malabsorption are considered the main factors responsible for BWL (14).…”
Section: Introductionmentioning
confidence: 99%
“…It correlates well with a decline in postoperative quality of life and is the most reliable indicator of malnutrition, which impairs immune function, infection susceptibility, and survival [1][2][3]. Although various mechanisms have been considered, such as the perturbation of absorption due to reduced pancreatic excretion [4,5], a decrease in the gastric acid level [6], reflux esophagitis [7], intestinal floral alteration [8], and increased peristalsis and diarrhea [9], reduced food intake [10,11] is the most conceivable explanation for weight loss after gastrectomy. To combat loss of appetite, surgeons dealing with gastric cancers have tried to increase food intake by producing a gastric substitute, such as a jejunal pouch, with limited success [12].…”
Section: Introductionmentioning
confidence: 99%